Hepatoprotective and antioxidant activity of hydroalcoholic extract of Stachys pilifera. Benth on acetaminophen-induced liver toxicity in male rats - Mansourian, Mahboubeh (Heliyon, 2019)
BACKGROUND: Acetaminophen (APAP) at high doses causes adverse side effects such as hepatotoxicity. The aim of the current study was to investigate the hepatoprotective and antioxidant effects of hydroalcoholic extract of Stachys pilifera. Benth (SP) on hepatotoxicity induced by APAP in male rats. METHODS: Adult male Wistar rats were allocated into four groups: control (C), APAP (2 g/kg), APAP + SP (500 mg/kg), and APAP + Silymarin (SM, 100 mg/kg) as positive control group. On the seventh day, the rats were sacrificed after taking blood samples. Then levels of biochemical parameters, oxidative stress markers and activity of antioxidant enzymes were measured. RESULTS: In the APAP group, aspartate aminotransferase (AST) and alanine aminotransferase (ALT) enzymes activity was significantly increased and the level of protein carbonyl (PCO) was insignificantly increased as compared to control group. In addition, the activity of glutathione peroxidase (GPX) and total thiol in the APAP group was significantly decreased compared to the normal rats. Stachys pilifera. Benth extract administration significantly reduced the activity of AST and ALT enzymes and the level of PCO compared to the APAP group, while significantly elevated the activity of GPX enzyme. CONCLUSION: Hydroalcoholic extract of SP diminishes hepatotoxicity induced by APAP by reducing the amount of liver function indicators (AST and ALT). Furthermore, the hydroalcoholic extract of SP is capable of reducing oxidative stress through inhibiting protein oxidation as well as boosting the activity of GPX enzyme. In this respect, the hepatoprotective impact induced by the SP extract may possibly be attributable to its reactive oxygen species scavenging and antioxidant properties.